Examining the factors affecting SME Performance: The Mediating Role of Social Media Adoption - Qalati, Sikandar Ali; Li, Wenyuan; Ahmed, Naveed; Mirani, Manzoor Ali; Khan, Asadullah (MDPI, 2021)
Small and medium enterprises (SMEs) have become a vibrant and dynamic sector of the world economy. Information technology plays a vital role in improving the productivity and competitiveness of SMEs. The dynamic business environment has brought fierce competition among SMEs and, therefore, requires the owners to interact with internal and external members actively. Hence, this study aims to investigate the impact of technology, organization, and environment as important factors in the performance of small and medium-sized enterprises. It also examines the mediating role of social media adoption. Items were developed to measure the various purposes of social media use in organizations, which contribute to increasing the measurement of social media usage. For the empirical investigation, this paper used a closed-ended questionnaire. Using a quantitative method, we observed 423 responses through structural equation modeling. The findings of the study indicate that technology, organization, and the environment play effective roles for SME performance. More importantly, social media adoption positively mediates the relationship between technology, organization, environment, and SME performance. The study also helps organizations realize the advantages of using social media and specifies the rationale behind an organization’s investment in social media.